Pengaruh Digital Marketing System, Terhadap Daya Saing Penjualan Susu Kambing Etawa - Akh Fawaid (Institut Agama Islam Negeri Madura, 2017)
In this research, the researcher wanted to know the influence of sales of goat milk Etawa using Digital Marketing System (Digital Sales system) and know the difference of conventional sales with Digital Marketing System. Easness Aspect of knowing the product, the content of Product, Benefits of product, and accelerate service process to consumer, Became one of the reasons Digital Marketing System used against Etawa Goat's milk sales. So it needs to be done experiment, to know the whole level of sales influence and competitiveness of Etawa Goat Milk Sales using Digital Marketing System and doing Comparison to sales using conventional system. The research method used is descriptive qualitative research method. The results showed, Digital Marketing System has a very high influence on sales of goat milk Etawa, compared using conventional system. One of them, on the marketing process, convenience and ease of consumers obtain product information, until the transaction process.